The Utilization of Garlic (Allium sativum Linn) and Red Ginger (Zingiber officinale var rubra) Extract on The Growth of Broiler were Infected by Escherichia coli - Ade Wildani Isma; Ma'ruf Tafsin; Yusuf Leonard Henuk; Nevy Diana Hanafi; Hamdan . (Universitas Sumatera Utara, 2017)
Abstract. This study aims to examine the effect of garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract on the growth of broiler chickens were infected by Escherichia coli. The design used in this study was a complete randomized design (CRD) with 6 treatments and 3 replications. Treatment consists of P0A = Control without infection; P0B = Control + E. coli infection; P1 = Infection E. coli + tetracycline antibiotics 0.05%; P2 = Infection E. coli + garlic extract (Allium sativum Linn) (1%); P3 = Infection E. coli + red ginger extract (Zingiber officinale var rubra) (1%); P4 = Infection E. coli + garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract (1%).The results showed that the effect of garlic and red ginger gave significant influence (P <0,05) to growth of broiler were infected by Escherichia coli. The combination of garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract has the highest influence of other activities. It was concluded that giving of garlic and red ginger extract give influence to growth of broiler were infected by Escherichia coli and can be used as alternative antibiotic.Abstract. This study aims to examine the effect of garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract on the growth of broiler chickens were infected by Escherichia coli. The design used in this study was a complete randomized design (CRD) with 6 treatments and 3 replications. Treatment consists of P0A = Control without infection; P0B = Control + E. coli infection; P1 = Infection E. coli + tetracycline antibiotics 0.05%; P2 = Infection E. coli + garlic extract (Allium sativum Linn) (1%); P3 = Infection E. coli + red ginger extract (Zingiber officinale var rubra) (1%); P4 = Infection E. coli + garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract (1%). The results showed that the effect of garlic and red ginger gave significant influence (P <0,05) to growth of broiler were infected by Escherichia coli. The combination of garlic (Allium sativum Linn) and red ginger (Zingiber officinale var rubra) extract has the highest influence of other activities. It was concluded that giving of garlic and red ginger extract give influence to growth of broiler were infected by Escherichia coli and can be used as alternative antibiotic.